Adhesion, Proliferation and Migration of NIH/3T3 Cells on Modified Polyaniline Surfaces - Rejmontová, Petra; Capáková, Zdenka; Mikušová, Nikola; Maráková, Nela; Kašpárková, Věra; Lehocký, Marián; Humpolíček, Petr (International journal of molecular sciences, 2016)
Polyaniline shows great potential and promises wide application in the biomedical field thanks to its intrinsic conductivity and material properties, which closely resemble natural tissues. Surface properties are crucial, as these predetermine any interaction with biological fluids, proteins and cells. An advantage of polyaniline is the simple modification of its surface, e.g., by using various dopant acids. An investigation was made into the adhesion, proliferation and migration of mouse embryonic fibroblasts on pristine polyaniline films and films doped with sulfamic and phosphotungstic acids. In addition, polyaniline films supplemented with poly (2-acrylamido-2-methyl-1-propanesulfonic) acid at various ratios were tested. Results showed that the NIH/3T3 cell line was able to adhere, proliferate and migrate on the pristine polyaniline films as well as those films doped with sulfamic and phosphotungstic acids; thus, utilization of said forms in biomedicine appears promising. Nevertheless, incorporating poly (2-acrylamido-2-methyl-1-propanesulfonic) acid altered the surface properties of the polyaniline films and significantly affected cell behavior. In order to reveal the crucial factor influencing the surface/cell interaction, cell behavior is discussed in the context of the surface energy of individual samples. It was clearly demonstrated that the lesser the difference between the surface energy of the sample and cell, the more cyto-compatible the surface is.
Keywords: Aniline Compounds; zvířata; biokompatibilní materiály; proliferace buněk; poly (2-acrylamido-2-methyl-1-propanesulfonic) acid; Animals; buňky NIH 3T3; Cell Adhesion; aniliny; Mice; povrchové vlastnosti; buněčná adheze; fibroblast; phosphotungstic acid; sulfamic acid; pohyb buněk; polyaniline; Surface Properties; Biocompatible Materials; Cell Movement; cyto-compatibility; myši; Cell Proliferation; NIH 3T3 Cells